Transcriptomics and Physiological Analyses of Soybean Stay-Green Syndrome - Dagang Wang; Yanan Wang; Ruidong Sun; Yong Yang; Wei Zhao; Guoyi Yu; Yueying Wang; Feng Wang; Lin Zhou; Zhiping Huang (Agronomy)
Stay-green syndrome (SGS) is an important factor that causes soybean (Glycine max) yield reduction. Despite progress being made, the regulatory mechanism remains largely unclear. Therefore, in this study, an SGS-sensitive soybean variety, “HD0702”, was employed to investigate the underlying mechanism. Transcriptomic analyses were performed in a tissue-specific manner to investigate differentially expressed genes (DEGs) in soybeans impacted by SGS and in those without SGS. A total of 1858 DEGs were identified in the pods, and 2814 DEGs were identified in the leaves. Further investigation revealed that SGS mainly affected the expression levels of key genes involved in the regulation of photosynthesis, starch and sucrose metabolism, and plant hormone signal transduction. To support this finding, the chlorophyll content of the pods was to be found increased by 320% for chlorophyll a and 260% for chlorophyll b. In leaves, soluble sugar levels significantly increased, whereas phytohormones IAA and ABA decreased in SGS pods. DEGs were classified using gene ontology (GO) terms, and photosynthesis-related genes α-glucosidase, β-mannosidase, β-amylase 5 (GmBAM5), and starch synthase 2 (GmSS2) were up-regulated. This study demonstrates a molecular and physiological basis for SGS that merits further investigation to allow for SGS management.